Characterization and Optimization of Field of View in a Holographic Waveguide Display - Zhongwen Shen; Yuning Zhang; Yishi Weng; Xiaohua Li (IEEE Photonics Journal, 2017)
The paper presents the characterization of the field of view (FOV) in a holographic waveguide display (HWD) with a broadband spectrum image source. The influences of parameters such as grating slanted angle of volume holographic grating (VHG), grating period, and effective refractive index are systematically analyzed. We optimized the parameters and calculated the maximum FOV of monochromatic and chromatic HWD. A multilayered VHGs structure is proposed to enlarge the FOV effectively without additional cost and optical design. We also build a rigorous simulation model to verify the feasibility of the multilayered structure. The theoretical maximum FOV of monochromatic and chromatic HWD are presented after optimization.